Transformações societárias em contexto pós-golpe de 2016 e suas implicações para formação presencial em serviço social no Rio Grande do Sul - Lampert, Michael da Costa (2020)
This dissertation is the result of a research carried out on the subject of presential training in Social Work in the state of Rio Grande do Sul at the PUCRS PPGSS. The research was driven by the following question: How do the current configurations of higher education in Brazil focus on training in presential courses of Social Work in RS? The starting point of this research has as its analytical focus the historical and political developments in the current conjuncture and took as its starting point the coup of 2016, and its repercussions in higher education and training in Social Service. It is, from the methodological point of view, a study with a mixed approach that combines quantitative and qualitative data. In methodologically approaching the object, the study considered analytical categories of reality based on the dialectic-critical method as a propelling element of the investigation, so that it synthesizes and expresses the contradictions and mediations that may contribute to the analysis of the movement of reality in which professional training in Social Work is constituted and is part. These categories emerge from the dialectical movement and contribute to explain reality, so that it transits through history, theory and method in order to elaborate a synthesis around the problem of research. The results of the research signal the tendency of formation as an expression of the mercantilization of higher education which, due to the political conjuncture favorable to the financial market expressly constituted after 2016, finds materiality mainly in the EC 95/2016 and its unfoldings that reconfigured the ways of life on a societal scale in Brazil. In this sense, the implications identified for the classroom training in Social Work in RS stands out in the following points: 1) The historical conditions in motion in the face of the post-war societal transformations in 2016 indicate a trend towards dismissal and/or transition from classroom training in private institutions to distance learning, revealing that classroom training in Social Work in Rio Grande do Sul will in future only prevail in courses of a public nature; 2) While the social impacts favor a conjuncture that is prone to the expansion of the EaD modality in the educational sphere, at a time when this modality takes on more strength in higher education and starts to dispute vacancies with the in-person HEIs, there was a constant tension about the new forms of education, mainly reflected in the reformulation and restructuring of pedagogical projects of courses, which started to reconfigure constantly according to the educational molds influenced by the financial market the form that this dimension in HEIs the neoliberal rationality expressed mainly in its competitive character; 3) Gradually, the constant reconfiguration put in place for face-to-face training is reflected in the dilapidation of critical training due to the ballast left by the competitive logic that has been occurring among HEIs, which aims to reduce costs and maximize results, i.e., tends to increasingly exploit the workforce of those who form new professional staff under precarious conditions. In this case, expressed in curricular flexibilizations and reformulations, adequacy of pedagogical projects added to the polyvalence of the work that appears for teaching social workers, where they must give account of teaching, research, extension, supervision of internship, orientation of works of conclusion of course, production of knowledge, planning of classes among other activities in time that the courses have been reducing their teaching staff, more and more work is carried out that focuses on what remains of these staff; 4) the impact on the working conditions of teaching social workers, reveal the abuse of the relative autonomy that social workers have to exercise their work in HEIs, in some cases, the institutional crossings that overload the work and impose flexibility and adjustments to the courses, therefore, demonstrate direct impacts on the quality of training of new professionals due to the tensioning of the model superimposed by higher education in its marketing sense to the professional project and training in Social Work, Consequently, these impacts hinder the formation of professional identity and later, may come to reflect a profile disqualified to exercise the profession, demonstrating that the HEI may come to chancel an uncompromising formation with what the category of Social Service historically constituted for its professional and training project. These results express the analysis of the reality that characterizes the configuration of the presential formation in RS. The research process carried out in this work resorted to theoretical and documentary sources and had the participation of social workers who coordinate courses in RS through online questionnaire to condense empirical data. In view of the reflections exposed, there is a need to intensify and foster the collective organization of the category of Social Service to defend in the scope of training and professional work, conditions of education and training based on the molds of critical social theory. This defense added to the production and dissemination of knowledge under this critical theoretical light is also a strategy to confront the neoliberal and market offensive identified in the investigative process. As a possible mediation possibility for the historical time experienced, a catalyst of resistance must be recognized in the entities representing the category, which, added to other segments of the working class that share values contributed to ethical principles of social service, beyond training, the defense of a model of education beyond capital as a flag of struggle is commitment and historical possibility both of approximation with common objectives for a more just societal order in the opposition of the neoliberal order, and the possibility of transforming the HEIs themselves, which has the university as an educational excellence and can contribute to the critical formation of the working class.